Agricultural Export Boom and Child Development: Evidence from Indonesian Palm Oil - Satya, Ardhian Prima; Edwards, Ryan (Jurnal sosial dan sains, 2025)
The global demand for palm oil has surged since the early 2000s, making Indonesia the world’s largest exporter. While this boom has contributed to rural economic growth, it has also raised concerns about increasing child labor and declining school participation in palm oil-producing regions. This study aims to analyze the causal effects of the palm oil export boom on child labor and schooling in Indonesia using district-level panel data from SUSENAS (2002 and 2010). A difference-in-differences (DiD) approach is employed, exploiting exogenous variation in global demand shocks and agro-climatic suitability for palm oil cultivation. The estimation results indicate that districts above the median suitability experienced an increase in child labor by 1.44% (significant at the 5% level) and a decrease in school attendance by 1.85% (significant at the 10% level). These findings underscore the unintended consequences of commodity booms on human capital development and call for targeted government interventions. Such policies should include stricter labor inspections, improved access to quality education, and efforts to eliminate child labor in high-risk rural regions.